Effect of Ground Motion Duration on the Seismic Response of Low- and Mid- Rise RC Buildings in Bangkok - Ruksilthong, Piyawat; Ornthammarath, Teraphan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
This paper examines the effect of seismic ground motion duration on design and risk of reinforced concrete buildings collapsing in Bangkok, Thailand. Reinforced concrete building models of 2 different heights, six-story and ten-story buildings are examined, which will simulate the natural period of buildings of 0.5 - 1.0 s. A nonlinear incremental dynamic analysis model was used to determine both the design level and the collapse levels. At the design level of shaking, it was discovered that the maximum interstory drifts, shear force, and overturning moments increased with increasing as ground motion duration. However, the increase of interstory drifts, shear force, and overturning moments does not exceed the seismic design standard for building (DPT.1301/1302). When records were scaled until the building collapse, it was discovered that scaling long duration records had a greater effect on building shaking than short duration records. Additionally, long duration records increase the probability of the building collapsing and has a lower collapse margin ratios than short duration records compared to the design spectrum. Additionally, it was discovered that long duration records have a larger impact when the building’s height or natural period increases.